Analysis the Role of References in Scientific Articles: Influence on Research Credibility and Impact - Fitriani Lubis; Darwita Arini Nasution; Debora Christine Girsang; Erika Sembiring; Hiskia Fitri S. Rumahorbo; Histi Trifesi Naibaho; Roni Frans David Simbolon; Sri Maryan Ariana Siregar; Tetty Rani Naibaho (PT FORMOSA CENDEKIA GLOBAL, 2023)
References are an important part of a logical article that upholds the statements, contradictions, and objectives conveyed by the author. References can also be used to avoid theft of literary works. This test is expected to dissect the reference function in logic articles, specifically its effect on the validity and influence of exploration. The research used qualitative methods with a literature review approach, and data were obtained from scientific articles published in accredited scientific journals. The results show that references play an important role in increasing the credibility and impact of research. Relevant and quality references can support the author's claims and arguments and help readers understand the research better. In this journal concludes that authors should pay attention to the quality and relevance of references used to increase the credibility and impact of research.